Insects associated with the genus Agave spp. (Asparagaceae) in Mexico - Rodríguez, William David; Navarrete-Heredia, José Luis; Vásquez-Bolaños, Miguel; Rodríguez-Macías, Ramón; Briceño-Félix, Guillermo Ariel; Blanco, Juana María Coronado; Ruíz-Cancino, Enrique (Zootaxa, 2019)
We present a synthesis of the insects reported associated with plants of the genus Agave L. (Asparagaceae) in Mexico, through a detailed review of published records. This work includes two checklists: the first include the species of insects collected in Agave, name of their hosts, their geographical distribution, notes on their biology and, references. Natural enemies of the insects associated with agaves are included in the second checklist with their geographical distribution, insect species host and, references. We found 273 species of insects collected in different Agave species. These species belong to 63 families and 7 orders. The orders of insects with the highest number of species are Coleoptera with 118 species and, Hemiptera with 65. The natural enemies of insects collected in agaves were 98 species from 18 families and 6 orders. The genera Aphytis and Encarsia (Hymenoptera: Aphelinidae) grouped the largest number of natural enemies of insects that were recorded in Agave with 15 and 10 species, respectively. Insects were collected from 42 species of Agave, of which 25 are endemic to Mexico. This study provides biological information on Mexican insects captured in Agave and, their natural enemies. The need for the conservation of these plants and associated insects is highlighted.